Ayurvedic Management of Vicharchika W.S.R to Eczema - Padwal, Komal Sudam; Salunkhe, Shraddha Anandrao; Shah, Sonal (International Research Journal of Ayurveda & Yoga, 2021)
Background All skin diseases were grouped together in the Ayurvedic text as Kushtarog. In modern dermatology, Vicharchika has a clinical appearance comparable to Eczema. Eczema (also known as atopic dermatitis) is characterized by dry, itchy skin with erythema and scaling that is poorly defined. Instead, symptomatic treatments such as steroids are used, which have serious side effects such as nephrotoxicity, osteoporosis, and skin cancer.Aims and Objective: To evaluate, elaborate and discuss etiology, Pathology and Management of Vicharchika. Material and methods- Brihatrayee, Laghutree, and other Ayurveda literatures, articles related to Vicharchika are compiled. Results- The purpose of this paper is to highlight the role of Ayurvedic Management in Vicharchika symptoms and recurrence. Conclusion- All Dosha, according to Ayurveda, must be in balance for good health. The symptom of eczema is treated with this product.. By cleansing vitiated Dosha and balancing the Dosha and Dhatus, Ayurveda treats the underlying cause of eczema.